Vedere, scrivere, raccontare La nozione di immaginazione a partire da Maurice Blanchot - Scarlato, Chiara (Aesthetica Preprint, 2023)
The paper aims at considering the issue of imagination through the analysis of some selected excerpts from the theoretical and fictional work of Maurice Blanchot. By adopting a perspective at the intersection between philosophy and literature, it will focus on some passages of the essay collections L’Espace littéraire (1955) and Le Livre à venir (1959), in association with a critical reading of the short stories L’idylle and Le dernier mot (written in 1935/1936 and both published in 1951). Moreover, it would assess that a comparison between Blanchot’s theoretical essays and fiction stories might help in clarifying the way in which the concepts of image, imaginary, and imagination concur to thematize the possibility of literature as such.